Magnetohydrodynamic flow of viscous fluid between two parallel porous plates with bottom injection and top suction. Issue 4 (12th March 2021) - Ganesh, S.; Delhi Babu, R.; Anand, V. W. J.; Chandrasekar, P.
ABSTRACT: This paper deals with the problem of steady laminar flow of an electrically conducting viscous incompressible fluid flow between two parallel porous plates of a channel in the presence of a transverse magnetic field with bottom injection and top suction. Uniform vertical flow is generated driven by a pressure gradient ∂ p / ∂ x . Vertical velocity is constant everywhere in the field flow, i.e. v  =  vw  = constant. The solution for small and large Reynolds number is discussed and the graph of a velocity profile for flow between a parallel porous plate with bottom injection and top suction is discussed.